La magia del charango In memoriam Celso Garrido-Lecca (1926-2025) - Yep Lenginnam, Virginia Beatriz (2026)
This text is a tribute to Maestro Celso Garrido-Lecca, a visionary composer who, through his example, awakened in me, as well as in many contemporary musicians, a love and respect for popular music, without setting it in opposition to academic music, but rather uniting the two into a single whole.